Prospective Comparison of Conventional External Dacryocystorhinostomy and Endonasal Laser Dacryocystorhinostomy - Faruque, S M Ahmed; Badrunnesa, Ashrafee Noor; Saha, Prionti; Mafi, Iftasham Ahmed; Shafi, Iftahaz Ahmed; Asaduzzaman, Md (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background:Epiphora, a common manifestation of chronic dacryocystitis, requires definitive treatment through dacryocystorhinostomy (DCR), a surgical procedure aimed at creating an alternative fluid drainage pathway.This study aimed to assess how effective both external dacryocystorhinostomy (Ex-DCR) and endonasal dacryocystorhinostomy (Endo-DCR) are in managing chronic dacryocystitis, with a specific focus on surgical duration, complication rates, and treatment outcomes. Methods: In this study, sixty participants were prospectively enrolled and evenly divided into two groups. Thirty patients were assigned to the first group and underwent En-DCR surgery, while the second group, also comprising thirty patients, underwent Ex-DCR surgery. Both groups were monitored for a duration of 9 months and assessed for surgical duration, perioperative and postoperative complications, and eventual surgical outcomes. Results: The distribution of patients across age groups and sexes was similar between the two groups (p>0.05). Clinical features such as epiphora, epiphora with discharge, and epiphora with swelling were comparable between groups. En-DCR group demonstrated significantly less intraoperative bleeding (mean:13.5 ml vs 50 ml; p<0.0001) and shorter operative durations (mean: 20 mins vs 37.5 mins; p<0.0001) compared to Ex-DCR group. Complications such as nasal bleeding and hematoma were minimal in both groups, with no significant differences noted. The final outcome, categorized as success (En-DCR vs Ex-DCR: 76.7% vs 83.3%) or failure (23.3% vs 16.7%), did not show a statistically significant difference between the two groups (p>0.05). Conclusion:Both surgical techniques offer feasible alternatives for addressing issues related to nasolacrimal obstruction. J Bangladesh Coll Phys Surg 2024; 42: 355-362